Big Data Management - Putu Suta Adya Dharma Rahadi; Kheri Arionadi Shobirin; Sri Ariyani (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2016)
In recent years, big data is a term representing large and complicated datasets that traditional data processing, including acquisition, pre-processing, storage, analytics, and visualization, etc, are not capable of tackling. Big data is a term that describes a large volume of data – both structured and unstructured – that inundates a business on a day-to-day basis. The usage of big data nowadays has deeply penetrated into various industries, such as e-commerce, retail, manufacturing, media, transportation, health-care, education, etc. In e-commerce, big data can be used in product ranking solution which offers solution to provide accurate information to the user based on their behavior when they are accessing any e-commerce website.